COPS: Calling Out Police to Suicide: Exploring How New Zealand Police Are Perceived as First Responders to Suicide by Those Experiencing Callouts - Hunter, Amanda (Auckland University of Technology, 2023)
Suicide is a serious issue across the globe. With police often being called as first responders to suicidal individuals, it is important to explore whether they are the best option for these types of callouts, especially when those with the highest rates of suicide are also those with the highest level of distrust in police. Through thematically analysed, semi-structured interviews, this study sought to determine if police were indeed the best first responders to suicide attempt callouts. Interviewees either had previously received a callout by police for a suicide attempt or were family members who had been involved in such a police callout. Five key research findings emerged. Firstly, the research found those who received a callout experienced poor police communication, both verbally and non-verbally. Secondly, police officers who respond to suicide callouts require improved training. Thirdly, police are not the ideal first responders unless the use of force is required. Fourthly, ideally, a team of health workers are the preferred first responders. Lastly, because using health workers only is currently not feasible, co-response teams are preferred over police-only callouts. While these findings are novel in the New Zealand context, they align with much of the overseas mental health literature. It is clear from both this study and prior research, that police are not the ideal responder for suicide callouts. Their poor use of communication including invalidating language, lack of training in mental health and suicide, and lack of procedural justice principles show that they can negatively impact suicide callouts. Instead, the co-response teams which are currently being trialled in New Zealand should become the new normal, with a plan to eventually move to a health-based callout system using police only in cases where the use of force is necessary.